The Systems Biology of Stem Cell Released Molecules—Based Therapeutics. (24th April 2013) - Maguire, Greg; Friedman, Peter
Abstract : Most therapeutics are based on the traditional method of reductionism where a clinically defined condition is broken down into a defined biochemical pathway underlying the condition, then a target in the pathway is identified, followed by developing a drug to interact with the target, modifying the target such that the disease is ameliorated. Biology acts as a system, therefore reductionist approaches to developing therapeutics are limited in therapeutic value because disease or traumatized tissue involves multiple underlying pathways, only a part of the pathways underlying the disease is manipulated by the traditional therapeutic. Much data regarding stem cells shows that their beneficial effects are not restricted to their ability to differentiate, but is more likely due in large part to their ability to release a multitude of molecules. Stem cells release potent combinations of factors that modulate the composition of the cellular milieu to evoke a multitude of responses from neighboring cells. Therefore, stem cells represent a natural systems-based biological factory for the production and release of a multitude of molecules that interact with the system of biomolecular circuits underlying an indication. Current research includes efforts to define, stimulate, enhance, and harness stem cell released molecules (SRM) to develop systems-therapeutics.